Identification of Ind transcription activation and repression domains required for dorsoventral patterning of the CNS - Von Ohlen, Tonia L. (2009)
Specification of cell fates across the dorsoventral axis of the central nervous system in Drosophila involves the subdivision of the neuroectoderm into three domains that give rise to three columns of neural precursor cells called neuroblasts. Ventral nervous system defective (Vnd), Intermediate neuroblasts defective (Ind) and Muscle segment homeobox (Msh) are expressed in the three columns from ventral to dorsal, respectively. The products of these genes play multiple important roles in formation and specification of the embryonic nervous system. Ind for example is known to play roles in two important processes. First, Ind is essential for formation of neuroblasts conjunction with SoxB class transcription factors. Sox class transcription factors are known to specify neural stem cells in vertebrates. Second, Ind plays an important role in patterning the CNS in conjunction with, vnd and msh, which is also similar to how vertebrates pattern their neural tube. This work focuses two important aspects of Ind function. First, we used multiple approaches to identify and characterize specific domains within the protein that confer repressor or activator ability. Currently, little is known about the presence of activation or repression domains within Ind. Here we show that transcriptional repression by Ind requires multiple conserved domains within the protein, and that Ind has a transcriptional activation domain. Specifically, we have identified a novel domain, the Pst domain, that has transcriptional repression ability and appears to act independent of interaction with the co-repressor Groucho. This domain is highly conserved among insect species, but is not found in vertebrate Gsh class homeodomain proteins. Second, we show that Ind can and does repress vnd expression, but does so in a stage specific manner. We conclude from this that the function of Ind in regulating vnd expression is one of refinement and maintenance of the dorsal border.